1992
DOI: 10.1038/ng0592-109
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant splicing of the CHM gene is a significant cause of choroideremia

Abstract: Choroideremia (CHM) is an X-linked progressive degeneration of the choroid and retina. 12% of unrelated male patients carry deletions of the partially cloned CHM gene. In Finland, there are more than 120 living CHM patients belonging to eight apparently unrelated pedigrees. Molecular deletions involving the CHM gene have been detected in three families. We have screened the remaining five families for point mutations. In one large family a single nucleotide (T) insertion into the donor splice site of exon C le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 10 publications
1
37
1
Order By: Relevance
“…Splice-donor site +3 mutations have been incriminated as the cause of human genetic disease in 14 other cases [6-17 and references therein]. Of the total, 3 are+3 A>T [8,12,17],as in our subject 4479, and 4 are +3insT [6,9,11,14], as in our subject 926203. The phenotypic consequence of the AR Intl(+3insT) or the Int6(+3A > T) mutation is complete androgen insensitivity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Splice-donor site +3 mutations have been incriminated as the cause of human genetic disease in 14 other cases [6-17 and references therein]. Of the total, 3 are+3 A>T [8,12,17],as in our subject 4479, and 4 are +3insT [6,9,11,14], as in our subject 926203. The phenotypic consequence of the AR Intl(+3insT) or the Int6(+3A > T) mutation is complete androgen insensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…The critical nature of the +3 splicedonor site position in normal mRNA processing is high lighted by the identification of 14 other +3 splice-donor site mutations in a variety of human genetic diseases [6][7][8][9][10][11][12][13][14][15][16][17], and references to +3 mutations therein].…”
Section: Introductionmentioning
confidence: 99%
“…Out of some 33 diseases, the chromosomal locus is known for 17, and the mutated gene identified for 15, (AGU, 208400) aspartylglucosaminidase [Ikonen et al, 1991] Choroideremia (303100) Rab geranylgeranyl transferase [Sankila et al, 1992] Congenital chloride diarrhea (CCD, 214700) chloride transporter [Höglund et al, 1996] Congenital nephrosis (CNF, 256300) nephrin ] Diastrophic dysplasia (DTD, 222600) sulfate transporter [Hästbacka et al, 1994b] Familial amyloidosis, Finnish type (FAF, 105120) gelsolin [Levy et al, 1990] Gyrate atrophy of choroid & retina (HOGA, 258870) ornithine Á-aminotransferase [Mitchell et al, 1989] Hypergonadotrophic ovarial dysgenesis (233300) follicle-stimulating hormone receptor [Aittomäki et al, 1995] Infantile neuronal ceroid lipofuscinosis (INCL, 256730) palmitoyl protein thioesterase [Vesa et al, 1995] Lysinuric protein intolerance (LPI, 222700) L-amino acid transporter [Lauteala et al, 1997] Nonketotic hyperglycinemia (NKH, 238300) glycine cleavage system; protein P [Kure et al, 1992 (600334) 2q [Haravuori et al, 1998] Usher syndrome, type III (276902) 3q most of them by positional cloning (table 1). According to expectations, all these disorders have shown extreme locus and allelic homogeneity.…”
Section: Finnish Disease Heritagementioning
confidence: 99%
“…In studies of European families with CHM, a total of 15 different mutations have been reported Sankila et al, 1992;Schwartz et al, 1993;Donnelly et al, 1994;van Bokhoven et al, 1994b) in the CHM gene. All the mutations, except one, result in the formation of a stop codon at the site of the mutation or create frameshift mutations that lead to premature stop codons.…”
Section: Introductionmentioning
confidence: 99%